Penguatan Peran dan Fungsi Manajemen Kepala Ruang Melalui Faktor Kepribadian dan Sosial Organisasi - Novita Kurnia Sari , Hanny Handiyani (Muhammadiyah Journal of Nursing, 2014)
Implementation of leader nurse in roles and functions management to nurses safety was infl uenced byseveral factors.The purposeof this studywere to investigate the most associating factors that related to implementation ofrolesandfunctions management of head nurse in the application of nursing safety. This study used correlativedescriptiveresearchmethod. The research samplewere 40 people and used total samplingtechniques. Personality factorsand socialorganizations havea signifi cant association withthe implementation ofrolesandfunctions management of head nurseto nursing safety application(p= 0,036andp=0,004). Personalityand socialorganizations neededthe attention of hospital managementthrough evaluation ofotherfactorsthat could be increasing the implementation of leader nurse roleand function management to application of nurses safety.